1985
DOI: 10.1115/1.3138511
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Local Blood Flow Velocity in Proximal and Distal Coronary Arteries by Laser Doppler Method

Abstract: A high resolution laser Doppler velocimeter using an optical fiber was developed to evaluate detailed characteristics of phasic blood flow in the coronary artery. Local blood flow velocities were measured in the proximal (0.27 +/- 0.05 cm i.d.) and the distal portion (0.09 +/- 0.02 cm i.d.) of the left circumflex coronary artery of anesthetized, open-chest dogs. The velocity waveform in the central axial region of the vessel and the velocity profile across the vascular lumen were compared in the proximal and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(27 citation statements)
references
References 0 publications
3
22
0
2
Order By: Relevance
“…Profiles of velocity in the plane of the myocardial curvature have been reported by several investigators using pulsed-Doppler ultrasound, 2728 laser Doppler anemometry, 29 and hot film anemometry. 28 There have been inconsistent observations as to the configuration of the velocity profiles in the coronary arteries.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Profiles of velocity in the plane of the myocardial curvature have been reported by several investigators using pulsed-Doppler ultrasound, 2728 laser Doppler anemometry, 29 and hot film anemometry. 28 There have been inconsistent observations as to the configuration of the velocity profiles in the coronary arteries.…”
Section: Discussionmentioning
confidence: 97%
“…Wells and associates, 28 using pulsed-Doppler ultrasound velodmetry, observed no skewing. Kajiya and associates, 29 using laser Doppler anemometry, showed inconsistent skewing of the velocity profile in the circumflex coronary artery of anesthetized dogs.…”
Section: Discussionmentioning
confidence: 98%
“…14 - 18 In previous studies, we have shown that the blood flow velocities in the proximal and distal coronary arteries 2 and in the great cardiac vein 6 can be successfully measured by inserting the optical fiber into the vessels with the aid of a light rubber cuff. Kilpatrick et aJ 19 also have shown the high level of accuracy of the laser Doppler anemometer with an optical fiber catheter for measurements of coronary sinus flow in the dog.…”
Section: Figure 8 Bar Graphs Showing Comparison Of Blood Flow Velocimentioning
confidence: 99%
“…There have been some studies on the flow pattern of CABG and most of them consist of experimental in vitro observations of the dye flow, 4 the two-dimensional simulation of CABG, 5 and the measurement of the flow quantity by laser Doppler or a magnetic flowmeter. [6][7][8][9] Computational fluid dynamics (CFD) has been a major tool for designing aircrafts, ships, and automobiles. CFD can demonstrate the rationality of the optimal flow in many complex problems, but has so far been only limitedly applied to designing cardiac surgery except for a few studies.…”
mentioning
confidence: 99%